Implementasi Kebijakan Ruang Penyimpanan Arsip Statis dalam Mendukung Preservasi Arsip Statis Berkelanjutan - Shirayuki, Livia; Wati, Nila Kurnia (Khazanah: Jurnal Pengembangan Kearsipan, 2025)
This study aims to describe the implementation of the Regulation of the Head of the National Archives of the Republic of Indonesia Number 23 of 2011, speciﬁcally concerning static archive storage space, which applies in the National Archives of the Republic of Indonesia (ANRI) environment in supporting sustainable static archive preservation. Maintaining stable temperature and humidity in static archive storage space is an obligation for an archival institution, considering that Indonesia is a tropical country. Unfortunately, maintaining stable temperature and humidity is still supported by facilities that are energy-consuming and have the potential to threaten environmental sustainability. This study is a descriptive qualitative study. Data collection involved interviews, observations, and document reviews relevant to this study. The results of the study indicate that the interests that inﬂuence the implementation of the static archive storage space policy are the interests of preserving the static archives themselves, so that the National Archives of the Republic of Indonesia is making great eﬀorts to achieve these interests. The implementation of this policy has provided beneﬁts in the form of preserving static archives, both in terms of physical and information contained therein. Resources in the form of facilities to maintain stable temperature and humidity in static archive storage space consist of an air conditioning system/ air conditioner (AC), dehumidiﬁer, sorb dry, electrical energy, and generator.